2010
DOI: 10.1016/j.jcis.2009.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of magnetic mesoporous particles

Abstract: Magnetic mesoporous particles were synthesized and their magnetic and structural properties are reported. The synthesis procedure consists of four steps: (i) preparation of magnetite colloidal nanoparticles; (ii) growth of a silica layer; (iii) development of the mesoporous structure and (iv) template removal. Two different methods for the template removal were studied and their effectiveness was discussed. Magnetization and Mössbauer spectroscopy measurements showed superparamagnetic behavior for the particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Furthermore, the magnetization does not saturate for this large value of the external field strength. Both results are signatures of small size superparamagnetic nanoparticle systems [28,35,39].…”
Section: Magnetizationmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, the magnetization does not saturate for this large value of the external field strength. Both results are signatures of small size superparamagnetic nanoparticle systems [28,35,39].…”
Section: Magnetizationmentioning
confidence: 87%
“…The analysis of the position and relative intensity of diffraction peaks suggests the formation of magnetite nanoparticles. However, due to the similarity between Fe 3 O 4 and γ-Fe 2 O 3 inverse spinel crystal structure, this analysis may not distinguish which of the iron oxides was actually formed [35]. One might think of using the position of 440 peak in order to identify the predominant magnetic phase.…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…Over the past several years, magnetic nanoparticles of iron oxides have gained increasing attention due to the wide variety of emerging applications of these easy to prepare biocompatible materials with favorable magnetic properties [1]. They have been extensively exploited as the materials of choice for magnetic resonance imaging (MRI), tissue-specific release of therapeutic agents as well as labeling and sorting of cells, and separation of biochemical products [2][3][4] for immobilization of enzymes or controlled and targeted drug delivery [5].…”
Section: Introductionmentioning
confidence: 99%
“…Morales et al reported the calcination of similar particles for template removal. 113 Although aggregate formation was observed even at relatively low calcination temperatures (300 C), the calcinated material revealed a very high specific surface area of 1023 m 2 g À1 . A similar procedure was used by Kim et al: (1) hydrothermal synthesis of a-Fe 2 O 3 particles, (2) coating with a dense SiO 2 layer, (3) subsequent formation of a mesoporous SiO 2 shell by the sol-gel reaction of tetraethoxysilane (TEOS) and n-octadecyltrimethoxysilane, (4) removal of the organic groups of n-octadecyltrimethoxysilane by calcination at 500 C. 114 The resulting mesoporous nanocomposite was loaded with Ni 2+ ions and treated at 500 C under H 2 /N 2 , thereby reducing hematite to magnetite, as well as producing Ni NPs on the surface.…”
Section: Silica-based Magnetic Compositesmentioning
confidence: 96%